Analisis Penerapan Big Data dalam Supply Chain Management: Systematic Literature Review - Syifa Alika Virgineta; Vina Dwiyanti; Aam Hamdani (Sci-tech Journal, 2025)
Implementation of big data in supply chain management, encompassing a wide range of critical sectors such as demand forecast, inventory management, logistics, and supplier relations. The advantages are numerous, including greater demand forecasting accuracy, increased visibility into the entire supply chain network, shorter lead times, and better risk management. Despite these benefits, problems emerge in the form of data security concerns, the need for specialized skills, and the complexity of integrating disparate systems. Overcoming these barriers is critical for companies that want to fully utilize big data, resulting in a more flexible, resilient, and customer-centric approach to supply chain operations.